Profile of Students’ Problem Solving Skills and Implementation Free Inquiry Model in Senior High School - Siti Meisaroh; Hainur Rasid Achmadi; Binar Kurnia Prahani (Universitas Lambung Mangkurat, 2020)
This study aims to determine the profile of students' problem-solving skills and the implementation of free inquiry models in high school. This type of research conducted using preliminary research methods with data collection techniques in the form of written tests filled out by students, student interview questionnaires, and teacher interview questionnaires. The data obtained were analyzed descriptively qualitatively. The study was conducted on 30 students of class XII Science 5 of Senior High School 1 Driyorejo. The results showed that only a few students used the strategy of problem-solving skills in solving Dynamic Electric problems. Of all students studied, 16 students had moderate category problem-solving skills ranging from 1.00-1.99, and 14 students had low category problem-solving skills with a range of 0.00-0.99. The lowest problem-solving skills criteria are at point C (conceptualize the strategy). So it can be concluded that the implementation of a free inquiry learning model assisted by virtual laboratories (PhET) in schools does not optimally cause students to be inactive in class so that the problem-solving skills of students are not in the high category.